Higher-order time integration schemes for the unsteady Navier–Stokes equations on unstructured meshes - Jothiprasad, Giridhar; Mavriplis, Dimitri J.; Caughey, David A. (Journal of computational physics, 2003)
The efficiency gains obtained using higher-order implicit Runge–Kutta (RK) schemes as compared with the second-order accurate backward difference schemes for the unsteady Navier–Stokes equations are investigated. Three different algorithms for solving the nonlinear system of equations arising at each time step are presented. The first algorithm (nonlinear multigrid, NMG) is a pseudo-time-stepping scheme which employs a nonlinear full approximation storage (FAS) agglomeration multigrid method to accelerate convergence. The other two algorithms are based on inexact Newton’s methods. The linear system arising at each Newton step is solved using iterative/Krylov techniques and left preconditioning is used to accelerate convergence of the linear solvers. One of the methods (LMG) uses Richardson’s iterative scheme for solving the linear system at each Newton step while the other (PGMRES) uses the generalized minimal residual method. Results demonstrating the relative superiority of these Newton’s method based schemes are presented. Efficiency gains as high as 10 are obtained by combining the higher-order time integration schemes such as fourth-order Runge–Kutta (RK64) with the more efficient inexact Newton’s method based schemes (LMG).